2023
DOI: 10.1038/s41598-023-34261-1
|View full text |Cite
|
Sign up to set email alerts
|

CD69 serves as a potential diagnostic and prognostic biomarker for hepatocellular carcinoma

Abstract: The prevalence and mortality of hepatocellular carcinoma (HCC) are still increasing. This study aimed to identify potential therapeutic targets related to patient prognosis. Data were downloaded from TCGA, GSE25097, GSE36376, and GSE76427 datasets. Differential analysis and enrichment analysis were performed in HCC. Cell deaths were evaluated, and least absolute shrinkage and selection operator regression (LASSO) regression was analyzed to screen candidate genes. Additionally, immune cell infiltration in HCC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…CD69 is signi cantly and positively correlated with T cells. The increased expression of CD69 may change the immunosuppressed tumor microenvironment into an immune state with a better prognosis, which may explain why HCC patients with high expression of CD69 had a better prognosis 21,22 . Besides, recent research has shown that BRI3 is identi ed as a new downstream target of the Wnt/ β-catenin signaling, which may be related to the poorer prognosis of HCC.…”
Section: Immune Analysis Of In Ltrated Immune Cells In Hcc By Scissormentioning
confidence: 99%
“…CD69 is signi cantly and positively correlated with T cells. The increased expression of CD69 may change the immunosuppressed tumor microenvironment into an immune state with a better prognosis, which may explain why HCC patients with high expression of CD69 had a better prognosis 21,22 . Besides, recent research has shown that BRI3 is identi ed as a new downstream target of the Wnt/ β-catenin signaling, which may be related to the poorer prognosis of HCC.…”
Section: Immune Analysis Of In Ltrated Immune Cells In Hcc By Scissormentioning
confidence: 99%